Chronic Malnutrition, Overweight and Obesity Among Rural Areaa Peruvian Children - Pajuelo Ramírez, Jaime (2000)
OBJECTIVES: To determine the prevalence of Chronic Malnutrition (CM), overweight and obesity among n rural area-peruvian children. MATERIALS AND METHODS: 1830 children of both sexes (aged 6 to 9 years) and who inhabit rural areas of Peru were studied. Body Mass Index (BMI) (w/h 2) was calculated. For CM determining the National Center for Health Statistics (NCHS) standard reference with the lesser than -2 SD diagnosis criterion was used. For BMI analysis Percentile Must et al classification was used, having as diagnosis values <5, 5-15, 15-85, 85-95, and >95 percentile, for deficit,low weight, normal, overweight, and abesity respectively. RESULTS: 49% of children presented CD. 10,4% had overweight and 2% obesity. Of children having CD 11,3% presented overweight and 2,2% had obesity. BMI correlation levels are high with weight (r=0,6) and low with height (r= 1). Linear Regression Analysis shows that BMI variations are given byjoint weight and height variations (r2=0,980), much lesser by weight alone (r2=0,380), and almost none variation by height alone (r2=0.01). CONCLUSIONS: These data emphasize the coexistence of overweight and obesity with growth retardation.